Teacher Reinforcements on Students’ English Learning Motivation - Alqadry, Nusul Anti; Muhayyang, Maemuna; Samtidar, Samtidar (Journal of Excellence in English Language Education, 2025)
The purpose of this research is to determine the effect of giving reinforcement on students' motivation to learn English. Researcher used a descriptive quantitative approach with an Ex-post facto research design without giving special treatment to research subjects. This research was conducted at UPT SMK NEGERI 6 Makassar at the XI Culinary 1 and 2 class levels, with a total population of 31 students. The sample of this study used all the existing population. The results indicated that teacher reinforcement was at a relatively low level, with an average score of 46.6, while students' motivation to learn English was at a moderate level, with an average score of 53.38. The results of the statistical analysis indicated that the impact of teacher reinforcement on student motivation was not statistically significant, with a regression coefficient (β1) of -0.044 and p-values of 0.720 from the t-test and F-test, which exceeded the 0.05 significance level. So, it fails to reject H0. Based on these results, it can be concluded that the teacher reinforcement given does not have a significant effect on student learning motivation.